Analisis Kinerja Keuangan Pemerintah Daerah di Wilayah Provinsi D.I Yogyakarta Tahun 2019-2021 - Muhammad Nazarudin Latief; Herlina Wijayanti; Iis Wijayanti; Kumba Digdowiseiso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study examines the financial health of local governments in Yogyakarta Province's Special Region from 2019 to 2021. By calculating the independence ratio, efficiency ratio, effectiveness ratio, harmony ratio—which is determined by comparing routine expenditure to development expenditure—and growth ratio, financial performance is evaluated. The local government budget (APBD) data from 2019 to 2021 in all regencies/cities within the Special Region of Yogyakarta Province is the secondary data source for this descriptive-quantitative research project.The efficiency ratio of Local Government Finance in the Special Region of Yogyakarta Province for the period of 2019-2021 is generally classified as efficient, with ratios below 100%, except for Bantul Regency and Gunung Kidul Regency, which showed a tendency of inefficiency in 2019 with a ratio of 101%. Considering the exception of Bantul Regency, which continually observed its effectiveness ratio fall from 2019 to 2021, the effectiveness ratio generally shows swings. Moreover, the priority of routine expenditure is greater than development expenditure, evident from the harmony ratio, with the average total ratio of routine expenditure being higher at 58% compared to the 42% of development expenditre. According to the growth ratio, all local governments in Yogyakarta Province's Special Region witnessed a decrease in growth in 2020 as a result of the Covid-19 epidemic. However, growth returned to positive territory in 2021, albeit it has not yet surpassed the level of 2019. Meanwhile, the independence ratio in DI Yogyakarta shows differences between the regencies/cities. The Yogyakarta City Government has an average independence ratio of 57.8%, indicating a